Relapse and The effort of Preventing Relapse to the ex-drug addiction - Khaerul Mahfud; Sulaiman Samad; Abdullah Sinring (Program Studi bimbingan Konseling PPs UNM Makassar, 2019)
The study aims to explain the relapse on the former drug addiction and its preventive efforts. The study used a qualitative method by a phenomenology approach. Data were collected by interviews and observations involving three subjects. The respondents were obtained by employing the snowball technique. The results of the study reveal that firstly, the first subject has experienced emotional and mental relapse (suggestion encouragement to return to taking drugs). While the second subject and the third experienced emotional, mental, and behavioral relapse (return to drug-consuming) after rehabilitation. Secondly, the factor causing emotional and mental relapse subject were namely the negative effects of drug addiction. While factor that supporting emotional, mental, and behavior relapse subject II and III experienced uncontrolled suggestion of mental relapse. Whereas, family support, social support, life lessons, happiness, life satisfaction, and better life expectancy the supporting factors of the subjects can be preventions of relapse. Thirdly, efforts to prevent relapse are conducting coping (problem-focused coping, positive religious coping, and emotional focused coping).